Clinical assessment of micronutrient deficiencies among children (1- 5 years) enrolled in anganwadis of old Hubli slums, Karnataka, India - Sarvar, Rana; Bant, D. D. (International Journal Of Community Medicine And Public Health, 2017)
Background: Micronutrients are vitamins and minerals required in small amounts that are essential to our health, development, and growth. As tiny as the amounts are, however, the consequences of their absence are severe. Iodine, vitamin A and iron are most important in global public health terms; their lack represents a major threat to the health and development, particularly children and pregnant women in low-income countries. The objectives were to clinically evaluate micronutrient deficiencies among children aged 1-5 years enrolled in anganwadi’s of old Hubli. Methods:A community-based cross-sectional study was carried out on 100 children enrolled in the anganwadis of Hubli slums for signs and symptoms of micronutrient deficiency. Results: Pallor was found in 78% children and delayed developmental milestones in 20% followed by delayed eruption of teeth in 17%. Among the studied group 37% had dry hair and dry skin. Vitamin A, B, C, D deficiency was seen in 1%, 29%, 14%, 38% respectively. Conclusions:The study concludes micronutrient deficiencies are prevalent among preschool children more so in with higher birth order having partial immunization. This appeals effective implementation of national health programmes, which can play a crucial role in addressing the hidden hunger. Correcting micronutrient deficiencies can significantly reduce childhood mortality and morbidity.